2012
DOI: 10.1111/tbj.12059
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Breast Cancer Subtypes, Ki-67 Proliferation Index, Age, and Pathologic Tumor Characteristics on Breast Cancer Survival in Caucasian Women

Abstract: Estrogen receptor (ER), progesterone receptor (PR), and epidermal growth factor receptor 2 (HER2) status are well-established prognostic markers in breast cancer management. The triple negative breast carcinoma subtype (ER-/PR-/HER2-) has been associated with worse overall prognosis in comparison with other subtypes in study populations consisting of ethnic minorities and young women. We evaluated the prognostic value of breast cancer subtypes, Ki-67 proliferation index (Ki-67PI), and pathologic tumor characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
43
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 28 publications
11
43
3
4
Order By: Relevance
“…This study also confirms the value of Ki67 evaluation as an objective means for prediction of prognosis as other recently published studies (Ferguson et al, 2013;Reyel et al, 2013;Strand et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…This study also confirms the value of Ki67 evaluation as an objective means for prediction of prognosis as other recently published studies (Ferguson et al, 2013;Reyel et al, 2013;Strand et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…In our database pathological, immunohistochemistry data and information about chemotherapy and hormonal and radiation therapy were collected. Several studies have shown that some variables such as age, grading, receptor status, and chemotherapy are independent risk factors for LRR (18). In our study, no significant correlations were found between these variables and LRR, OS and DFS, with the exception of PR expression in regard to better LRR (p=0.011).…”
Section: Discussioncontrasting
confidence: 84%
“…Ki67 is an emerging prognostic factor that seems to adversely influence outcome of patients with N1 disease; Ferguson and colleagues have shown that the proliferative index is one of the most important prognostic factors, but as yet it is not possible to tailor therapies according to the Ki67 value (18). In our study, the Ki67 index at the cut-off of >14% did not appear to affect DFS nor LRR.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…CHD5 was more frequently methylated in breast tumor samples with ER/PR (or both) negative status than in samples with ER/PR (or both) positive status. The ER/PR status has been recognized as a prognostic factor in patients with breast carcinoma, and has been noted to be a predictive marker for the response to treatment with endocrine therapy (27). The presence of ER and PR is predictive of the response to treatment with the anti-estrogen drug tamoxifen (28).…”
Section: Discussionmentioning
confidence: 99%